VALIDATION OF THE DIGITAL ELEVATION MODEL (SRTM) WITH GNSS SURVEYING APPLIED TO THE MIRIM LAGOON HYDROGRAPHIC BASIN - Scalco, Patricia Andréia Paiola; Iescheck, Andrea Lopes; Corrêa, Iran Carlos Stalliviere; Scottá, Fernando Comerlato; Oliveira, Rafael Mastracusa de; Franchini, Ricardo Augusto Lengler (Boletim de Ciências Geodésicas, 2018)
Between 2013 and 2014, a kinematic positioning based on the Global Navigation Satellite System (GNSS) was carried out for this research work. This GNSS survey resulted in 275916 points with tridimensional coordinates in the cross-border basin area of 58205km2 called Mirim Lagoon Hydrographic Basin, located in south of Rio Grande do Sul (Brazil) and west of Uruguay. This study aims at showing the methodology firstly and, furthermore, results regarding the validation of the vertical accuracy of the DEM SRTM through kinematic positioning by GNSS, in the Mirim Lagoon Hydrographic Basin region. Also, the GNSS surveying data was post-processed with the Precise Point Positioning (PPP) method, and the ellipsoidal height was converted into orthometric height through the software INTPT geoid. During this study, the geopotential model (EGM96) was used to transform altitude differences between two countries, Brazil and Uruguay. Results showed that the vertical mean absolute error of the DEM SRTM vary from 0.07m to ± 9.9m with average of -0.28 m. This vertical accuracy is better than the absolute vertical accuracy value of ±16m published in the SRTM data specification and validates the DEM SRTM.